2019
DOI: 10.1371/journal.pone.0211891
|View full text |Cite
|
Sign up to set email alerts
|

Motivating household water conservation: A field experiment in Singapore

Abstract: We test and compare different incentives in motivating water conservation using a randomized controlled trial. In a field experiment carried out with Singaporean households, regular feedback was given, with informative, normative and monetary incentives provided to different groups. Evidence shows that all households saved an average of 4 Litres of water per person per day, with no difference in treatment effect found across various groups. Perhaps unsurprisingly, the water saving effect is also found to be mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 21 publications
3
28
0
2
Order By: Relevance
“…The policy area where incentives are used are mostly waste, energy and water and are often effective compared to control groups and other types of treatment [16,46,105]. This is consistent with other meta-analytic studies that found significant effects of incentives for energy and waste sectors [27,57].…”
Section: Incentivessupporting
confidence: 83%
“…The policy area where incentives are used are mostly waste, energy and water and are often effective compared to control groups and other types of treatment [16,46,105]. This is consistent with other meta-analytic studies that found significant effects of incentives for energy and waste sectors [27,57].…”
Section: Incentivessupporting
confidence: 83%
“…Working with the Public Utilities Board (PUB, a statutory board under MEWR), scholars from the National University of Singapore recently conducted a field experiment to assess the effectiveness of various forms of information on water conservation. Over 1 month, the researchers periodically placed door hangers representing different treatment conditions on the main entrance of more than 900 households (Goette et al, 2019). There were two different kinds of information presented: water conservation tips that were framed as a campaign and normative feedback (i.e., household usage and efficient use benchmarks).…”
Section: Nudging In the Domain Of The Environmentmentioning
confidence: 99%
“…For example, previous studies have shown that employees who have received letters about their expected pensions save more for retirement in Germany (Dolls et al 2018), but not in the U.S. (Carter and Skimmyhorn 2018). In the context of water use, the effect of providing conservation tips varies widely across studies, from 1% (Ferraro and Price 2013) up to 2 to 5% (Goette et al 2019, Tonke 2020). Even more drastically, studies on information provision to conserve energy have found effect sizes ranging from less than −10 to about 8% (see e.g.…”
Section: Introductionmentioning
confidence: 99%